Pandemic racism: describing and delegitimising discursive necropolitics on Africa in Danish mainstream media during COVID-19 - Ravn, Amalie (Department of Psychology, 2024)
This is an interdisciplinary study that combines critical psychology with necropolitics, feminist, queer and crip theory, as well as linguistics through discourse theory and media studies through analysis of news articles to examine how everyday discourse contributes to practices of violence that continue to make race real. Its framework The theoretical framework of the study is necropolitics at large, Achille Mbembe's original necropolitical framework reworked through decolonial, queer and feminist critiques to create an eclectic necropolitical lens that is calibrated for the analysis of pandemic discourse. The main argument is discussed through the critical discourse analysis of Danish mainstream media's production of African figures in the context of the COVID-19 pandemic in 2020. The study shows that necropolitical discourse of the black and African body and nation act as a constitutive supplement to the configuration and mapping of white bodies, white supremacy and national identity. These configurations are characterised by productions of ‘Africa' as a death world, marked by suffering, unsafety and disease, which are produced and made comprehensible within white, nationalist formations of Denmark as a world of life marked by health, security and supremacy. This study concludes that the discursive creation of ‘Africa' is co-constructed and intertwined with the creation of Denmark, suggesting that distinctions between mechanisms of exclusion and mechanisms of inclusion dissolve in ways that disrupt key epistemic assumptions of normative psychology.